Recycled concrete and brick powders as supplements to Portland cement for more sustainable concrete. (1st September 2022) - Likes, Lauren; Markandeya, Ananya; Haider, Md Mostofa; Bollinger, David; McCloy, John S.; Nassiri, Somayeh
Abstract: This study presents the successful implementation of eco-friendly recycled powders (RPs) in concrete based on extensive experimental data to promote the reuse of these RPs as supplementary cementitious materials to lower cement demand and reduce associated CO2 emissions. The fine fraction of recycled concrete aggregate and brick waste was used to produce recycled concrete powder (RCP) and recycled brick powder (RBP) by ball milling. The RPs were ranked significantly weaker in pozzolanic/hydraulic activity relative to fly ash, slag, and a natural volcanic pozzolan based on the bound water, chemical shrinkage testing, and calcium hydroxide consumption, but they passed the strength activity index (SAI) criterion of 75% at seven and 28-d. Their use in concrete at 20% replacement by mass of the cement was successful, with RBP and RCP showing SAI of 92% and 86% on seven days, 98% at 28 days, and 105% and 100% at 56 days. RBP also positively impacted durability with an increased surface resistivity of 24% over the control. The results of this study show that RBP and RCP, with weak pozzolanic activity, could still positively affect the mechanical properties of concrete and could potentially follow a recycling path as supplementary cementitious materials.